2004
DOI: 10.1021/ja0463886
|View full text |Cite
|
Sign up to set email alerts
|

Structure, Reactivity, and Density Functional Theory Analysis of the Six-Electron Reductant, [(C5Me5)2U]2-η66-C6H6), Synthesized via a New Mode of (C5Me5)3M Reactivity

Abstract: The sterically crowded (C(5)Me(5))(3)U complex reacts with KC(8) or K/(18-crown-6) in benzene to form [(C(5)Me(5))(2)U](2)(mu-eta(6):eta(6)-C(6)H(6)), 1, and KC(5)Me(5). These reactions suggested that (C(5)Me(5))(3)U could be susceptible to (C(5)Me(5))(1-) substitution by benzene anions via ionic salt metathesis. To test this idea in the synthesis of a more conventional product, (C(5)Me(5))(3)U was treated with KN(SiMe(3))(2) to form (C(5)Me(5))(2)U[N(SiMe(3))(2)] and KC(5)Me(5). 1 has long U-C(C(5)Me(5)) bond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
206
1
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 226 publications
(225 citation statements)
references
References 95 publications
17
206
1
1
Order By: Relevance
“…(Diaconescu and Cummins, 2012) In the case of uranium all reduced arene complexes had an analogous electronic structure, featuring  overlap between LUMOs of one phenyl ring and the 83 two uranium centers. Other related diuranium inverse sandwich benzene or toluene complexes that were synthesized with different supporting ligands adhere to similar bonding considerations (Arnold et al, 2012;Diaconescu et al, 2000;Evans et al, 2004;Monreal et al, 2011;Mougel et al, 2012;Patel et al, 2011).…”
Section: Group 3 Metal Stilbene Complexesmentioning
confidence: 93%
See 3 more Smart Citations
“…(Diaconescu and Cummins, 2012) In the case of uranium all reduced arene complexes had an analogous electronic structure, featuring  overlap between LUMOs of one phenyl ring and the 83 two uranium centers. Other related diuranium inverse sandwich benzene or toluene complexes that were synthesized with different supporting ligands adhere to similar bonding considerations (Arnold et al, 2012;Diaconescu et al, 2000;Evans et al, 2004;Monreal et al, 2011;Mougel et al, 2012;Patel et al, 2011).…”
Section: Group 3 Metal Stilbene Complexesmentioning
confidence: 93%
“…This suggestion, based on the Lewis acid character of thorium is in line with what is described in section 2, where several benzene/arene polyanions stabilized by coordination to lanthanides are presented. For actinides, several groups reported that benzene or its derivatives can serve as a bridging ligand between two uranium ions (Arnold et al, 2012;Diaconescu et al, 2000;Diaconescu and Cummins, 2012;Evans et al, 2004;Monreal et al, 2011;Patel et al, 2011).…”
Section: Synthesis and Structural Characterization Of Rare Earth Biphmentioning
confidence: 99%
See 2 more Smart Citations
“…For actinides, several groups reported that benzene or its derivatives can serve as a bridging ligand between two uranium centers 11,[14][15][16][17][18][19] . Magnetic susceptibility measurements, X-ray absorption near edge structure (XANES) spectroscopy and density functional theory (DFT) studies showed that most of these complexes can be described as having a benzene (or a substituted benzene) dianion bridging two U(III) centers 14,16 . A [toluene] 4 À uranium complex was reported by Liddle and coworkers 11 ; the evidence presented there, however, does not allow an irrefutable interpretation of its electronic structure.…”
mentioning
confidence: 99%